How to be an illustrator - Rees, Darrel (London Laurence King Publishing, 2014)
Offers practical guidance to aspiring illustrators, including effective ways to approach would-be clients, how to negotiate contracts, and how to set up a studio.
The broad and social church of illustration -- Getting started -- Preparing your portfolio -- Job-hunting and interviews -- Producing the first job -- Billing it : financial tips -- Studios -- Agents.
Previous edition 2008.
Includes bibliographical references (pages 162-166).
Keywords: Illustrators -- Vocational guidance; Commercial artists -- Vocational guidance